2019
DOI: 10.1093/ejo/cjz043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of labial fixed appliance orthodontic treatment on patient expectation, experience, and satisfaction: an overview of systematic reviews

Abstract: Summary Background Patient perception with fixed appliance orthodontic treatment is important to improve oral health-related quality of life. Objective The main objective of this study was to evaluate the impact of labial fixed appliance orthodontic care on patient perception before, during, and after the treatment. Search methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
1
18
0
1
Order By: Relevance
“…Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low . This suggests that in many areas, the methodological quality of SR is low or critical low.…”
Section: Discussionmentioning
confidence: 94%
“…Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low . This suggests that in many areas, the methodological quality of SR is low or critical low.…”
Section: Discussionmentioning
confidence: 94%
“…Esthetic improvement is the primary motive for adult patients seeking orthodontic treatment. 4,5 The orthodontic need assessments in Saudi Arabia have revealed that crowding was the most common malocclusion trait, followed by increased overjet and spacing. 6 It has been reported that the 40-62.4% of the population needs orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Is this primarily due to non-compliance? Fixed functional appliances theoretically eliminate the problem of cooperation, but are more prone to breakage and are more expensive [ 66 , 67 , 68 , 69 ]. A 2021 article reported a high level of compliance with the AMCOP device, despite augmented salivation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%